Aplicación de descargas simultáneas de alto voltaje y arco eléctrico para el tratamiento superficial avanzado de metales (2014)
The three-dimensional ion implantation (3DII) is a plasma method which is developed to treat metal surfaces. This method is realized in the JUPITER (Joint Universal Plasma and Ion Technologies Experimental Reactor) device through a low pressure pulse discharge ignited on the left branch of the Paschen curve. The main objective of the method is to improve the tribological characteristics of metal surfaces. To protect the material surfaces exposed to aggressive media, the JUPITER Device is modified with an installation of an arc electric vaporizer in its chamber. This modification permits to generate the high voltage discharge in the titanium vapor atmosphere. In this work a hybrid discharge (high voltage and electric arc discharges in simultaneous functioning) is studied and the experimental data show that the treatment of the AISI SAE 1020 steel surfaces by titanium ion and atom flows significantly reduce the damages produced by sulfate-reducing bacteria (BSR).